Forecasting Tools for Analyzing Urban Land Use Patterns and Truck Movement: Case Study and Discussion of Results. Issue 1 (2016) - Wygonik, Erica; Bassok, Alon; McCormack, Edward; Goodchild, Anne; Carlson, Daniel
Many urban planning efforts have supported development in dense, mixed-use areas, but tools are not widely available to help understand the relationship between urban form and goods movement. A review is presented on the status of urban goods movement forecasting models to account for the impacts of density and mixed land use. A description is given of a series of forecasting model runs conducted with state-of-the-practice tools available at the Puget Sound Regional Council. By comparing dense, mixed-use scenarios with different baseline and transportation network alternatives, the ability of the model to capture the relationship between goods movement and density is evaluated. The paper concludes with a discussion of the implications of the results for truck forecasting and freight planning.